Historicized presents. Senses about the Argentine genocide (1983-2014) - Silveyra, Malena (Revista Mexicana de Ciencias Políticas y Sociales, 2021)
This article analyzes the main explanatory models of the Argentine genocide (1976-1983) between 1983 and 2015, understanding that the disputes over the sense of the past are articulated with the common sense of present society, enabling particular modes of appropriation or alienation of those experiences For this purpose, the category of structure of meaning has been constructed in order to account for the central conflict in each narrative, identifying the different elements that compose it and their relationships. In the period analyzed, four structures of meaning were identified: "two demons" and "pacification", characterized by a binary explanation; “Genocide,” which proposes a historization that transcends the military dictatorship, and “state terrorism”, which articulates the previous ones.